2011
DOI: 10.1007/s11661-011-0858-x
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Thermal and Chemical Activation with Cerium Salts of the Alloy AA2017 in Aqueous Solutions of NaCl

Abstract: A wide variety of anticorrosive treatments for aluminum alloys that can be employed as ''green'' alternatives to those based on Cr(VI) are currently under development. This article reports a study of the morphological and anticorrosive characteristics of surface layers formed on the AlCu alloy AA2017 by immersion treatment in baths of cerium salt, accelerated by increased temperature and the employment of hydrogen peroxide. Scanning electron microscopy (SEM)/ X-ray energy dispersive spectroscopy (XEDS) studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…It is known that the formation of cerium-based conversion coatings proceeds over and around intermetallic particles, both anodic and cathodic against the aluminium matrix, although via different mechanisms depending on the electrochemical behaviour of the intermetallic [31]. It has been also described that the coating forms on other electrochemically active areas such as grain boundaries or rolling marks made during manufacturing [11,43,44]. In our work, on one hand, microanalysis by SEM-EDS of samples CeCC-1 and CeCC-2 with 15 min and only 3 min of cerium treatment confirmed that Al(Cu,Mg) intermetallic and Al-Cu-Fe-Mn-(Si) phases are seeds for the deposition of the coating, as described in Figures 6-8.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the formation of cerium-based conversion coatings proceeds over and around intermetallic particles, both anodic and cathodic against the aluminium matrix, although via different mechanisms depending on the electrochemical behaviour of the intermetallic [31]. It has been also described that the coating forms on other electrochemically active areas such as grain boundaries or rolling marks made during manufacturing [11,43,44]. In our work, on one hand, microanalysis by SEM-EDS of samples CeCC-1 and CeCC-2 with 15 min and only 3 min of cerium treatment confirmed that Al(Cu,Mg) intermetallic and Al-Cu-Fe-Mn-(Si) phases are seeds for the deposition of the coating, as described in Figures 6-8.…”
Section: Discussionmentioning
confidence: 99%
“…Los intermetálicos Al(Cu,Mg) inicialmente presentan un comportamiento anódico. Posteriormente, como se ha observado mediante SEM-EDX, durante el tratamiento en Smut Go sufren desaleación de Mg, y el consiguiente enriquecimiento en Cu de los mismos modifica su comportamiento a catódico (Aballe et al, 1998, Obispo et al, 2000Zhu y Van Ooij, 2003;Lacroix et al, 2008;Bethencourt et al, 2009;Bethencourt et al, 2012). Por su parte, los intermetálicos Al(Cu,Fe,Mn,Si) presentan un comportamiento catódico desde el comienzo.…”
Section: Discussionunclassified
“…The protective effect was also evaluated in terms of resistance and pseudo-capacitance of the conversion layers; adjusted for the EIS data, the results, as functions of the RE concentration (0.01,0.1, 0.5, and 1 g L −1 ) for the bath temperature and immersion time that yielded the highest electrochemical performance, are shown in Figure 11 From Figure 11 and equation 7, it was computed that the average improvements of Rp for the CeCCs are 11.10 ± 0.54, 70.75 ± 3.58, 29.12 ± 1.45, and 50.55 ± 1.45 times, using an ion concentration of 0.01, 0.1, 0.5, and 1.0 g L −1 , correspondingly; whereas for the same concentration for lanthanum, the In summary, it has been established that treatments of AA6061 aluminum alloys by thermal activation up to 70°C in a RE(NO 3 ) x ion solution with a concentration lower than 0.5 g L −1 allow the formation of an oxide/hydroxide layer over the intermetallic and aluminum oxide composite film that covers the metal matrix [56] with sufficient thickness and uniformity to provide a higher level of protection than the room temperature treatments. As a consequence, R p is increased to large values depending on an adequate combination of ion concentration, and bath immersion time, although this last variable above 600 min exhibits a small contribution to the barrier properties.…”
Section: CXmentioning
confidence: 93%